Influence of age at surgery on left ventricular strain in patients with anomalous origin of left coronary artery from pulmonary artery. (13th December 2022) - Kakarla, Saikiran; Sasikumar, Deepa; Varma, Ravi Prasad; Kurup, Harikrishnan K N; Gopalakrishnan, Arun; Nair, Krishna Kumar Mohanan; Dharan, Baiju S; Krishnamoorthy, Kavasseri M
Abstract: OBJECTIVES: Myocardial strain abnormalities are described after surgical repair of anomalous left coronary artery from pulmonary artery (ALCAPA) even after recovery of ventricular function. The factors that predispose to the presence of these strain abnormalities in the presence of normal ventricular function are unknown. The aim of this study was to find out whether the age at repair influences the presence of global and regional strain abnormalities on follow-up. METHODS: Repaired ALCAPA patients from a single centre ( n = 40) with good ventricular ejection fraction on follow-up were recruited. Baseline and follow-up data were collected from electronic records. Global and regional myocardial strain assessment was done by speckle tracking echocardiography prospectively. The association between age at repair and strain abnormalities on follow-up was analysed. RESULTS: The patients who presented earlier had significantly worse ventricular function pre-operatively compared to older patients ( P < 0.0005). Global longitudinal strain was abnormal in 40% of patients with normal ventricular ejection fraction on follow-up. Presence of longitudinal strain abnormalities was more in patients who underwent repair at older age than in those who were repaired earlier ( P < 0.0005). The probability of having normal longitudinal strain on follow-up was 81.6% if surgery was done before 7.8 months of age. If operated before 6 months, the odds of having normal myocardial strain was 11 times higher. Regional strain abnormalities of varying severity were present in all patients in the left and in some patients in the right coronary artery territories. CONCLUSIONS: Older age at ALCAPA repair is associated with increased incidence of myocardial strain abnormalities. Regional strain abnormalities were found in both left and right coronary artery territories. Abstract : Left ventricular systolic function normalizes after surgical repair in most of the patients with anomalous left coronary artery from pulmonary artery (ALCAPA) [1–4].